Comparative assessment of bronchial asthma control level in patients aged 12 to 17 years old of EsSalud Arequipa - Arturo Recabarren Lozada; Elvira Parishuaña Calcina; Nadia Martínez Murillo; Grimaneza Esquía Moroco (Horizonte Médico, 2017)
Objective: This was an observational, cross-sectional and prospective study to compare the bronchial asthma control level in pediatric patients aged 12 to 17 years old who take part in the Hospital III Yanahuara – EsSalud Arequipa’s Asthma Program and have the same control level achieved in other EsSalud Arequipa’s health care centers, according to the internationally validated instrument named “Asthma Control Test” (ACT). Materials and methods: A sample was taken from 60 patients distributed into two groups: one of them consisted of 30 patients who took part in the Hospital Yanahuara Pediatric Unit’s Asthma Program and the other one of 30 outpatients from other EsSalud’s pediatric health care centers. For the purpose of the analysis, proportionality was maintained with regard to gender and asthma severity in both groups. Results: The average ACT score was 22.27 in the group who took part in the Hospital III Yanahuara’s Asthma Program and 20.17 in the group of outpatients who went to other pediatric health care centers. The most frequent score was 25 for the first group and 23 for the second one. More than half of the patients from both groups achieved an acceptable score in the disease control test. Nevertheless, “total control” was mainly achieved by patients who took part in a preventive program (26.67% versus 6.67%) and “poor control” was mainly observed in children assessed in a pediatric outpatient consultation (36.66% versus 16.66%). Conclusions: The vast majority of children who take part in an asthma control preventive program achieve a total or acceptable asthma control with a statistically significant difference.